Positive solutions of the diophantine equation - W. R. Utz (International Journal of Mathematics and Mathematical Sciences)
Integral solutions of x3+λy+1−xyz=0 are observed for all integral λ. For λ=2 the 13 solutions of the equation in positive integers are determined. Solutions of the equation in positive integers were previously determined for the case λ=1.